Functional MRI of the vocalization-processing network in the macaque brain - Ortiz-Rios, Michael; Kuśmierek, Paweł; DeWitt, Iain; Archakov, Denis; Azevedo, Frederico A. C.; Sams, Mikko; Jääskeläinen, Iiro P.; Keliris, Georgios A.; Rauschecker, Josef P. (Frontiers in Neuroscience, 2015)
Using functional magnetic resonance imaging in awake behaving monkeys we investigated how species-specific vocalizations are represented in auditory and auditory-related regions of the macaque brain. We found clusters of active voxels along the ascending auditory pathway that responded to various types of complex sounds: inferior colliculus (IC), medial geniculate nucleus (MGN), auditory core, belt, and parabelt cortex, and other parts of the superior temporal gyrus (STG) and sulcus (STS). Regions sensitive to monkey calls were most prevalent in the anterior STG, but some clusters were also found in frontal and parietal cortex on the basis of comparisons between responses to calls and environmental sounds. Surprisingly, we found that spectrotemporal control sounds derived from the monkey calls (“scrambled calls”) also activated the parietal and frontal regions. Taken together, our results demonstrate that species-specific vocalizations in rhesus monkeys activate preferentially the auditory ventral stream, and in particular areas of the antero-lateral belt and parabelt.